Pengaruh Pemanasan dan Ethylen Glycol pada Elektrodeposisi Lapisan Tipis Magnetite menggunakan Continue Direct Current: Sylvina Tebriani, Syukri, Dahyunir Dahlan - Sylvina Tebriani, Sylvina Tebriani; Syukri, Syukri; Dahyunir Dahlan, Dahyunir Dahlan (Jurnal Fisika dan Aplikasinya, 2025)
Magnetite (Fe3O4) film was successfully deposited on a ITO substrat by Electrodeposition (ED) technique use a Continue Direct Current (CDC). XRD characterization show that the heating process is very influences the formation of a thin layer of magnetite. Magnetite deposited with FCC structure with crystal size of 32.617 nm to 185.521 nm, under the control of the surfactant concentration of the solvent. Deposition parameter optimum is refined crystal size and minimum surface roughness. Lattice parameter of each sample is 8.313 , 8.365 , 8.354 , 8.351 , slightly lower than the standard value 8375 (JCPDS # 01-088-0315). While the spacing the crystal planes were obtained in the range of 2.507 to 2.522 . SEM characterization results showed that magnetite is spread evenly over the substrate Indium Tin Oxide (ITO). Three samples (A, C, D) deposited in the form of aggregates of magnetite crystals. While the Q sample deposited in the form of layer.